KOMPETENSI SOSIAL GURU DI MADRASAH IBTIDAIYAH ALKHAIRAAT KOTA GORONTALO: Indonesia - Saifulhaq Inaku; Doly Hanani; Muhammad Nur Iman (Irfani, 2021)
ABSTRACT This study will see and observe how the Social Competence of Teachers at Madrasah Ibtidaiyah Alkhairaat Gorontalo City in developing teacher competencies so that gradually they reach the level of competent or professional teachers. In this case, the moral motivation of the principal is not enough, but concrete steps and policies are needed regarding programs related to the development of competence, professionalism and teacher needs, as the demands of the government and society on the quality of education today, especially the quality of teachers. Competent teachers will carry out teaching and learning tasks in the classroom with enthusiasm and fun, and full of meaning; students always get something new every time they enter class to learn. Students will never be bored to learn in class because the teacher is competent. In the end, competent teachers will produce students who study hard because they love the learning process and understand the importance of learning for their future. This research uses descriptive method that is fact finding with proper interpretation . Teachers at Madrasah Ibtidaiyah Alkhairaat Gorontalo City have good social competence. This can be seen when the teacher interacts and communicates with the principal, fellow teachers, education staff, students, parents/guardians of students and the community around the madrasa. In carrying out the education process, teachers of Madrasah Ibtidaiyah Alkhairaat Gorontalo City have carried out components of social competence, namely: Teachers are inclusive, act objectively, and are not discriminatory because of considerations of gender, religion, race, physical condition, family background, and socioeconomic status. This journal certainly has shortcomings, therefore constructive criticism and suggestions are highly expected for its perfection.